Public Housing Saving Program: A Comparative Legal Analysis between Indonesia and Singapore - Nurmala, Sheila Adi; Utami, Ikawati (Indonesian Comparative Law Review, 2024)
This study aims to identify the inherent problems of the Public Housing Savings program (Tapera) and seeks solutions through law reforms to improve the effectiveness, transparency, and accountability of the program. This normative legal research employs comparative approach by analyzing the similar programs in Singapore. The Housing Development Board (HDB) in Singapore is selected as benchmark to evaluate the performance and regulation of Tapera in Indonesia. The study also applies a functional approach to explore the function and purpose of legal frameworks of Tapera and their impact in the implementation of the program. The results show that despite changes made through Government Regulation No. 21 of 2024 to improve Tapera's performance, there are still significant problems, including low public participation, transparency and accountability issues, and controversies related to mandatory contribution payments. This research emphasizes the importance of comprehensive and inclusive law reforms that take into account social and economic aspects to ensure that Tapera can be more effective in helping people own their own homes, as well as fulfilling the state's constitutional obligation to provide adequate housing for all citizens.